Metabolic mediators: microbial-derived metabolites as key regulators of anti-tumor immunity, immunotherapy, and chemotherapy - Lu, Shan; Wang, Chunling; Ma, Jingru; Wang, Yichao (Frontiers in Immunology, 2024)
The human microbiome has recently emerged as a focal point in cancer research, specifically in anti-tumor immunity, immunotherapy, and chemotherapy. This review explores microbial-derived metabolites, emphasizing their crucial roles in shaping fundamental aspects of cancer treatment.Metabolites such as short-chain fatty acids (SCFAs), Trimethylamine N-Oxide (TMAO), and Tryptophan Metabolites take the spotlight, underscoring their diverse origins and functions and their profound impact on the host immune system. The focus is on SCFAs' remarkable ability to modulate immune responses, reduce inflammation, and enhance anti-tumor immunity within the intricate tumor microenvironment (TME). The review critically evaluates TMAO, intricately tied to dietary choices and gut microbiota composition, assessing its implications for cancer susceptibility, progression, and immunosuppression. Additionally, the involvement of tryptophan and other amino acid metabolites in shaping immune responses is discussed, highlighting their influence on immune checkpoints, immunosuppression, and immunotherapy effectiveness. The examination extends to their dynamic interaction with chemotherapy, emphasizing the potential of microbial-derived metabolites to alter treatment protocols and optimize outcomes for cancer patients. A comprehensive understanding of their role in cancer therapy is attained by exploring their impacts on drug metabolism, therapeutic responses, and resistance development. In conclusion, this review underscores the pivotal contributions of microbial-derived metabolites in regulating anti-tumor immunity, immunotherapy responses, and chemotherapy outcomes. By illuminating the intricate interactions between these metabolites and cancer therapy, the article enhances our understanding of cancer biology, paving the way for the development of more effective treatment options in the ongoing battle against cancer.